Carrots and Rainbows: Motivation and Social Practice in Open Source Software Development1 - von Krogh, Georg; Haefliger, Stefan; Spaeth, Sebastian; Wallin, Martin W. (MIS Quarterly, 2012)
Open source software (OSS) is a social and economic phenomenon that raises fundamental questions about the motivations of contributors to information systems development. Some developers are unpaid volunteers who seek to solve their own technical problems, while others create OSS as part of their employment contract. For the past 10 years, a substantial amount of academic work has theorized about and empirically examined developer motivations. We review this work and suggest considering motivation in terms of the values of the social practice in which developers participate. Based on the social philosophy of Alasdair MacIntyre, we construct a theoretical framework that expands our assumptions about individual motivation to include the idea of a long-term, value-informed quest beyond short-term rewards. This motivation–practice framework depicts how the social practice and its supporting institutions mediate between individual motivation and outcome. The framework contains three theoretical conjectures that seek to explain how collectively elaborated standards of excellence prompt developers to produce high-quality software, change institutions, and sustain OSS development. From the framework, we derive six concrete propositions and suggest a new research agenda on motivation in OSS.